THE ROLE OF CORPORATE SOCIAL REPORTING IN STATE-OWNED COMPANIES - A. Bottaev (Вестник университета)
An increasing number of companies are paying attention to the social and sustainability reporting. These concepts characterize the economic activities of the company include information on the results of these activities, as well as social and environmental performance. Corporate social reporting is a tool for informing shareholders, employees, contractors, customers and the public about the pace of implementation of the company incorporated in the strategic plan of development goals in terms of achieving economic stability, social stability and favorable ecological conditions.